PP150 The Role Of Expert Consensus In UK Guidance: Patient Selection For Hydrogel Spacer Use During Prostate Cancer Radiotherapy. (23rd December 2022) - Saunders, Rhodri; Payne, Heather Ann; Jain, Suneil; Peedell, Clive; Edwards, Albert; Thomas, Andrew; Das, Prantik; Hedblom, Amanda Hansson; Woodward, Emily; Bahl, Amit
Abstract : Introduction: In UK males, prostate cancer is the most common cancer, with over 47, 500 diagnosed annually. Radiotherapy is a highly effective curative treatment but can be limited by dose to surrounding normal-tissues such as the rectum. Radiation to the rectum can be reduced by increasing the distance between prostate and rectum with a hydrogel spacer. Despite National Institute of Health and Care Excellence guidance, spacers are not widely funded in the UK. Limited funding has necessitated patient prioritization, without any existing consensus on method. Studies have shown generally homogenous results in reduction of rectal toxicity across assessed subgroups, but the requirement to prioritize remains. One way of addressing the appropriate use of beneficial health technologies is the inclusion of end-user experts in decision-making. The study aim was to identify consensus among radiation oncologists on patient prioritization for rectal hydrogel spacers. Methods: We conducted a Delphi study where six leading clinical oncologists and one urologist from across the UK experienced in using rectal hydrogel spacers participated in two rounds of online questionnaires and two virtual advisory board meetings. Results: The experts estimated that 83 percent of patients who could potentially benefit from a spacer were denied access. Overall, ten points of consensus were reached. Key ones concerning patient-access were: Spacer use in eligible patients significantly reduces radiation dose to the rectum and toxicity-related adverse events. Increased benefit is expected in patients on anticoagulation, with diabetes and with inflammatory bowel disease. Increased benefit can be expected with ultra-hypofractionated radiotherapy, but radiotherapy modality is not a key consideration for patient selection. Patients should have the opportunity to actively participate in the discussion regarding the use of a spacer. Conclusions: Currently, not all patients who would benefit can access funding for hydrogel spacers. Consensus in this study indicates that appropriate health policy and funding mechanisms are warranted for patients, to provide equitable access to technologies improving quality of life.